Pelaksanaan Tanggung Jawab Orang Tua Terhadap Anak Akibat Putusnya Perkawinan - Fakri Putra, M.; Triganda Sayuti, Ageng (Universitas Jambi, Fakultas Hukum, 2023)
The purpose of this study was to determine and analyze the implementation of parental responsibility towards children due to the break-up of marriage at the Jambi Religious Court and legal responsibility for parents who did not carry out their obligations after the breakup of the marriage. This research includes juridical empirical research, which examines the gap between das sollen and das sein or the gap between what is supposed to be according to law and the reality in the field. The location of the study, namely the Jambi Religious Court Office, were the population parties in this study. Sampling in this study using purposive sampling technique. There is still a lot of parental lack of awareness about the responsibilities after the breakup of marriage to their children. In particular, male parents or ex-husbands have not fully fulfilled their obligations in terms of providing support for their children after the break-up of the marriage. Therefore, for parents who do not carry out their obligations to the child, a request for execution can be made later, in which the court will first call and when after being given a warning by the court, they still have not carried out their obligations, the court will execute the parents who did not. carry out its obligations.